2015
DOI: 10.3389/fmed.2015.00079
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thrombocytopenic Purpura Secondary to Cytomegalovirus Infection: A Case Report

Abstract: Immune thrombocytopenic purpura (ITP) is defined as an acquired thrombocytopenia with antibodies detected against platelet surface antigens, and it is the most common form of thrombocytopenia in otherwise asymptomatic adults. ITP secondary to an underlying condition is a diagnosis of exclusion that is essential to establish for treatment efficacy. Secondary thrombocytopenia caused by cytomegalovirus (CMV) is common; however, case reports associated with diagnosis in immunocompetent adults are rare, and to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…The clinical picture consists of symptoms such as: general malaise, myalgia, headache, fever. Clinical syndromes such as pneumonia, encephalitis, retinitis, uveitis, colitis may be associated [10].…”
Section: Resultsmentioning
confidence: 99%
“…The clinical picture consists of symptoms such as: general malaise, myalgia, headache, fever. Clinical syndromes such as pneumonia, encephalitis, retinitis, uveitis, colitis may be associated [10].…”
Section: Resultsmentioning
confidence: 99%
“…Immune (idiopathic) thrombocytopenic purpura is an autoimmune disease characterized by the destruction of thrombocytes or suppression of their production as a result of an immune reaction with thrombocyte membrane autoantigens [ 1 ]. Therapy is required when the thrombocyte count falls below 20,000/mm 3 or if there are symptoms such as mucosal or vaginal hemorrhage when the count is in the range 20,000–50,000/mm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic immune thrombocytopenic purpura (ITP) is an autoimmune disease characterized by an immune response to thrombocyte membrane antigens. ITP is generally treated with surgery and steroids [ 1 ]. Situs inversus totalis is a rare congenital abnormality in which all of the mediastinal and abdominal organs are transposed to mirror symmetry of the normal anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is a serious cause of morbidity and mortality among immune compromised patients. 7 Several studies have suggested that infection with CMV might be closely associated with the pathogenesis of immune thrombocytopenia; [8][9][10] however, it has also been reported that there is no obvious correlation between the resolution of thrombocytopenia and CMV clearance. 11 Though the mechanism by which a CMV-induced thrombocytopenia may occur remains unclear, the implication of CMV in the pathogenesis of thrombocytopenia could be explained by several theoretical mechanisms.…”
Section: Introductionmentioning
confidence: 99%